Introduction to rings and modules - Musili C (Calcutta Narosa Pub, 1992)
Acquisition: Acquisition works include ordering, receiving, inspection, accessioning, and processing of bills etc. Presently, acquisition is decentralized. Acquisition Unit is responsible for MC (excluding Serials). STA, WCL is responsible for acquisitio
Keywords: Modules; Ring theory